The Use of Tense and Aspect in Arabic: A Comparison of Educational Research Articles by Native and Non-Native Speakers - Supriadi, Rinaldi; Sudana, Dadang; Kurniawan, Eri; Nurmala, Mia; Meftahi, Maria (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2024)
This article explores the difference of tense and aspect use in Arabic academic writing by native and non-native speakers, driven by the challenges non-native speakers face in accurately conveying temporality in academic contexts. Improving non-native proficiency in Arabic grammar is crucial for enhancing the clarity of their research output. The study data consisted of academic articles written by both groups, specifically focusing on the results and discussion sections. Through qualitative analysis, findings revealed that native speakers demonstrate a strong grasp of grammar, with balanced use of past and present tenses and appropriate aspects, effectively expressing both completed and ongoing actions. In contrast, non-native speakers, particularly those from Indonesian backgrounds, tend to overuse the present tense and active voice, indicating difficulties in fully understanding Arabic’s temporal aspects. These results underscored the need for more intensive language instruction focused on mastering Arabic tense and aspect structures to improve non-native academic writing skills.